Collusion and delegation under information control - Andreas Asseyer (Freie Universität Berlin, School of Business & Economics, 2020)
This paper studies how information control affects incentives for collusion and optimal organizational structures in principal-supervisor-agent relationships. I consider a model in which the principal designs the supervisor's signal on the productive agent's private information and the supervisor and agent may collude. I show that the principal optimally delegates the interaction with the agent to the supervisor if either the supervisor's budget is large or the value of production is small. The principal prefers direct communication with the supervisor and agent if the supervisor's budget is sufficiently small and the value of production is high.
Keywords: D73; D83; D86; H57; M55; 330; Collusion; Information design; Delegation